The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/0104-6632.20140314s00002655
|View full text |Cite
|
Sign up to set email alerts
|

Wet oxidation of glycerol into fine organic acids: catalyst selection and kinetic evaluation

Abstract: -The liquid phase oxidation of glycerol was performed producing fine organic acids. Catalysts based on Pt, Pd and Bi supported on activated carbon were employed to perform the conversion of glycerol into organic acids at 313 K, 323 K and 333 K, under atmospheric pressure (1.0 bar), in a mechanically agitated slurry reactor (MASR). The experimental results indicated glycerol conversions of 98% with production of glyceric, tartronic and glycolic acids, and dihydroxyacetone. A yield of glyceric acid of 69.8%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The kJ/mol, respectively, the value ranges of which are well consistent with previous reports on the same reaction. [28,54,55] Importantly, we find that the presence of Fe lowers the activation energies for primary and secondary oxidation on Pt catalyst. The activation barrier for lactic acid formation is almost unchanged but that for C−C cleavage is much lower on bimetallic PtFe(1) catalyst.…”
Section: Pt and Fe Element Dispersion Within Bimetallic Clustersmentioning
confidence: 74%
“…The kJ/mol, respectively, the value ranges of which are well consistent with previous reports on the same reaction. [28,54,55] Importantly, we find that the presence of Fe lowers the activation energies for primary and secondary oxidation on Pt catalyst. The activation barrier for lactic acid formation is almost unchanged but that for C−C cleavage is much lower on bimetallic PtFe(1) catalyst.…”
Section: Pt and Fe Element Dispersion Within Bimetallic Clustersmentioning
confidence: 74%
“…These models are commonly used realistic approach to derive the rate expression for heterogeneous reactions. The selection of models was based on the analysis of literature data on the kinetic modeling of the conversion of glycerol into PG [37], LA [38,39] and other carboxylic acids [40] in an alkaline media.…”
Section: Proposed Kinetic Modelmentioning
confidence: 99%
“…Varma's group investigated reaction network for glycerol conversion to various carboxylic acids on PtBi/C catalysts . Due to complex reaction network for the formation of a variety of C 1 to C 3 acids, a progressive modeling methodology was employed for each sub‐network with oxalic acid, glycoxalic acid, dihydroxyacetone, glyceric acid and glycerol as initial reactants.…”
Section: Figurementioning
confidence: 99%
“…Brainer and colleagues studied oxidation kinetics on PdPtBi/C trimetallic catalysts. A mechanism involving adsorption of glycerol and acids on one type of site with O 2 on another site is proposed and validated with experimental data . Zaera and coworkers studied glycerol oxidation on Pt/SiO 2 catalyst and found that the observed changes are mainly due to a reversible poisoning of the catalyst by dihydroxyacetone (and possibly other primary products) …”
Section: Figurementioning
confidence: 99%